A CMOS ultra-wideband impulse radio transceiver for 1-mb - Terada, T. (IEEE Journal of solid state circuits)
A CMOS ultra-wideband impulse radio (UWB-IR) transceiver was developed in 0.18-μm CMOS technology. It can be used for 1-Mb/s data communications as well as for precise range finding within an error of ±2.5 cm. The power consumptions of the transmitter and receiver for data communication are 0.7 and 4.0 mW, respectively. When an LNA operates intermittently through bias switching, the power consumption of the transceiver is only 1 mW. The range for data communication is 1 m with BER of 10-3. For ranging applications, the transmitter can reduce the power to 0.7 μW for 1k pulses per second, and the receiver consumes little power. The transceiver design, all-digital transmitter, and intermittent circuit operation at the receiver reduce the power consumption dramatically, which makes the transceiver well suited for applications like sensor networks. The electronic field intensity is lower than 35 μV/m, and thus the UWB system can be operated even under the current Japan radio regulations.